Effectiveness of Photovoltaic Solar Cells against Light Wavelength by Irradiating Method of R-G-B Lamp - Parlindungan Pandapotan Marpaung; Adi Setiawan (JURNAL ILMU PENGETAHUAN DAN TEKNOLOGI (IPTEK), 2014)
Sunlight visible color of white light is composed of light color% mixture of light colors red (R), % lightcolor green (G) and % color blue light (B) is called a basic light color mixture (R+G+ B). Sunlight shining on the surface of the solar cell PV cells convert solar cell produces a voltage at the output referred voltage Voc. In this research, the irradiation treatment surface of each of three samples of the same type solar cells with light colors red, green and blue alternately. Samples used solar cells have the characteristics of the open circuit voltage Voc parameters = 6 volts dc reference voltage Voc expressed as (ref). Each of the three R-G-B light color lamp is connected to a variable dc voltage source in volts. Electrical power R-G-B lights shining on the solar cell is set as large, on PL(R) = PL(G) = PL(B) = 2.27 watts. Radiation treatment each R-G-B light onto the surface of the three samples of solar cells with a distance = 7 cm, the measurement results obtained voltage Voc(R) [average] = 2.91 volts, Voc(G) [average] = 2 , 40 volts, and Voc(B) [average] = 3.02 volts at the output of the solar cell. The effectiveness of PV cells (photovoltaic) is obtained from the comparison of Voc(R) [average-2], Voc(G) [average] and Voc(B) [average] against a reference voltage Voc = 6 volts. Solar cell conversion results obtained irradiating light of each color of R-G-B generate % red light (R) = 34.94 %, % green light (G) = 28.8 % and the % of blue light (B) = 36.2 %. The effectiveness of PV cells to convert solar cell material believed color red, green and blue is expressed by the parameter PV(R), PV(G) and PV(B). Thus obtained PV(R) = 34.9 %, and PV(G) = 28.8 % and further PV(B) = 36.2 %.